Local energy self-sufficiency for passive buildings: Case study of a typical Moroccan building. (May 2020) - Chegari, Badr; Tabaa, Mohamed; Moutaouakkil, Fouad; Simeu, Emmanuel; Medromi, Hicham
Abstract: The building sector in Morocco represents about 25% of the country's total energy consumption, including 18% for the residential sector and 7% for the service sector. The integration of renewable energies in the building sector is the subject of a major trend in terms of future projects in Morocco. Today, Morocco is targeting a strategy that will allow it to achieve 50% of its electricity consumption from a renewable, new and clean local energy source. Through this current situation, this article has just made a positive contribution, by studying the impact of the passive part of a typical Moroccan R+1 building, in particular that of thermal insulation, on its energy self-sufficiency in different climates. TRNSYS simulation studio was used to design and develop a platform to calculate this objective in a global and specific way. This platform combines a whole hybrid system, based on two new and clean renewable energy sources (wind turbine and photovoltaic energy), to the building's thermal loads. The results show that the impact of thermal insulation on the building's energy self-sufficiency in all the studied climates is very significant, especially in Ifrane city (Morocco). Given that the energy self-sufficiency in this climate has been improved by 41.28% more than the baseline situation. Finally, we suggest that the Moroccan building thermal code should include the impact of the passive part of the building on its energy self-sufficiency in the form of numerical indicators, in order to encourage people to get involved in this development. Highlights: A platform that allows to evaluate the improvement actions of the passive part of the building on its energy self-sufficiency has been developed. Mathematical modeling of each component used in the platform is described. The impact of thermos-physical parameters of thermal insulations on the building's energy performance is assessed in different climates. The impact of the most efficient thermal insulation on the building's energy self-sufficiency is assessed in different climates.